Seismic soil-structure interaction in multi-span bridges application to a railway bridge. - Carbonari, Sandro (Earthquake engineering & structural dynamics.)
The effects of soil structure interaction on the seismic response of multi-span bridges are investigated by means of a modelling strategy based on the domain decomposition technique. First, the analysis methodology is presented : kinematic interaction analysis is performed in the frequency domain by means of a procedure accounting for radiation damping, soil-pile and pile to pile interaction; the seismic response of the superstructure is evaluated in the time domain by means of user-friendly finite element programs introducing suitable lumped parameter models take into account the frequency-dependent impedances of the soil-foundation system. Second, a real multi-span railway bridge longitudinally restrained at one abutment is analyzed. The input motion is represented by two sets of real accelerograms : one consistent with the Italian seismic code and the other constituted by five records characterized by different frequency contents. The seismic response of the compliant-base model is compared with that obtained from fixed-base model. Pile stress resultants due to kinematic and inertial interactions are also evaluated. The application demonstrates the importance of performing a comprehensive analysis of the soil foundation structure system in the design process, in order to capture the effects of soil structure interaction in each structural element that may be beneficial or detrimental.